2018
DOI: 10.1016/j.neuroimage.2017.11.025
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of resting state fMRI measures to classify individual patients with Alzheimer's disease

Abstract: Alzheimer's disease (AD) patients show altered patterns of functional connectivity (FC) on resting state functional magnetic resonance imaging (RSfMRI) scans. It is yet unclear which RSfMRI measures are most informative for the individual classification of AD patients. We investigated this using RSfMRI scans from 77 AD patients (MMSE = 20.4 ± 4.5) and 173 controls (MMSE = 27.5 ± 1.8). We calculated i) FC matrices between resting state components as obtained with independent component analysis (ICA), ii) the dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
138
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(149 citation statements)
references
References 68 publications
8
138
0
1
Order By: Relevance
“…Advancements have been made in image acquisition and capacity to algorithmically sort images trained by a constellation of image and patient features. 56,57 Difficulties with learning, cognition, depression, or anxiety are well-recognized comorbidities of epilepsy. 47 Thus, it is unclear to what extent this could improve upon expert interpretation.…”
Section: Future Directionsmentioning
confidence: 99%
“…Advancements have been made in image acquisition and capacity to algorithmically sort images trained by a constellation of image and patient features. 56,57 Difficulties with learning, cognition, depression, or anxiety are well-recognized comorbidities of epilepsy. 47 Thus, it is unclear to what extent this could improve upon expert interpretation.…”
Section: Future Directionsmentioning
confidence: 99%
“…GGMs were recently applied as clustering algorithm for brain networks in a few other single-modality applications. De Vos et al [de Vos et al, 2017] found them useful for increasing group separation between AD and controls compared to classical Pearson correlation networks in resting-state functional connectivity. Titov et al [Titov et al, 2017] compared metabolic networks for the differential diagnosis between AD and frontotemporal lobar degeneration (FTLD).…”
Section: Alterations Of Graph Measuresmentioning
confidence: 99%
“…Jiang et al, 2019;Santarnecchi et al, 2014) and chronological age (Dosenbach et al, 2010;Liem et al, 2017). To model the RSFC-phenotype association, three prediction models including connectome-based predictive modeling (CPM), support vector regression (SVR) and least absolute shrinkage and selection operator (LASSO) have been frequently adopted for their good performances and interpretabilities (Coloigner et al, 2016;de Vos et al, 2018;R. Jiang et al, 2019;Meng et al, 2017;Ryali et al, 2012;Shen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%